A new Ypsilopus (Orchidaceae, Angraecinae) from Zimbabwe and notes on the parallel evolution of extreme column exsertion in African angraecoids - Farminhão, João; Cribb, Phillip J. (Plant ecology and evolution, 2023)
Background and aims – A preliminary review of hawkmoth-pollinated angraecoids from Africa unveiled a remarkable case of parallel evolution of extreme column exsertion between the two species formerly classified in in the defunct genus Barombia . These belong to one clade of Aerangis , including A. gracillima and A. stelligera , and Ypsilopus sect. Barombiella, including Y. amaniensis and Y. schliebenii . The exploration of the geographical distribution of these two clades, followed by an examination of morphological variation within Y. sect. Barombiella, revealed that the disjunct population identified as Y. amaniensis from Zimbabwe represents an undescribed species. Material and methods – Occurrence records of Ypsilopus amaniensis , Y. schliebenii , Aerangis gracillima , and A. stelligera were comprehensively mapped and distribution patterns were visually analysed. Pollination syndromes and pollinaria attachment sites were inferred based on a review of floral and hawkmoth morphology. Standard herbarium practices and mining of photographs of wild and cultivated plants in social media allowed the description of the novelty. Key results – Ypsilopus zimbabweensis sp. nov. (Y. sect. Barombiella) is a narrow endemic of significant horticultural interest and it is preliminarily assessed as Endangered. The evolution of a Barombia -type column presents a parallel geographical pattern in the Aerangis gracillima – A. stelligera clade and Ypsilopus sect. Barombiella and probably induced a shift of pollen placement sites in these sphingophilous species.